NET ZERO EMISSION CONTINGENCY FOR 2060 IN JAKARTA: A BIBLIOMETRIC ANALYSIS - Richard Andre Sunarjo; Lavalette Erica Sunarjo (Faculty of Economics and Business Universitas Pelita Harapan, 2026)
As Indonesia's capital and economic center, Jakarta faces unprecedented challenges in aligning rapid urbanization with climate commitments. Indonesia has pledged to achieve Net Zero Emissions (NZE) by 2060, establishing a critical imperative for Jakarta's urban decarbonization strategy. This bibliometric analysis examines 156 articles and proceedings across nine years of publication (2017–2026) from the Dimensions database to map the scholarly landscape of Jakarta's NZE 2060 contingency planning. Using co-citation networks, keyword co-occurrence analysis, and thematic mapping via VOS viewer two dominant research clusters emerged: (1) Urban Energy Transition, emphasizing solar photovoltaic integration and smart grid modernization; (2) Climate Resilience and Adaptation, addressing flood mitigation and sea-level rise vulnerability centered on the Long-Term Strategy for Low Carbon and Climate Resilience (LTS-LCCR). A significant research gap was identified regarding contingency pathways during economic or environmental shocks, suggesting that while Jakarta's decarbonization roadmap is well-documented, scholarship on adaptive resilience mechanisms remains underdeveloped